2008
DOI: 10.1590/s1413-70542008000500002
|View full text |Cite
|
Sign up to set email alerts
|

Adubação nitrogenada em cobertura no girassol irrigado nas condições de Cassilândia-MS

Abstract: O nitrogênio é o nutriente mais requerido pelas plantas por assumir funções importantes no metabolismo vegetal. Na cultura do girassol, sua deficiência causa desordem nutricional, sendo o nutriente que mais limita a produção. Além disso, doses elevadas podem aumentar a incidência de pragas e doenças afetando a produção de grãos. Conduziu-se o experimento com o objetivo de avaliar a resposta da cultura do girassol (Helianthus annuus L.) irrigado, submetido a diferentes doses de nitrogênio aplicado parceladament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
4
65

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 5 publications
3
36
4
65
Order By: Relevance
“…Similar results were presented by Lobo et al (2012), who concluded that the increment in N levels from 50 to 130 kg ha -1 increased sunflower productivity from 2,152 to 3,802 kg ha -1 . These results also agree with those of Biscaro et al (2008), who observed that split N fertilisation as top-dressing at the doses of 0 to 80 kg ha -1 increased the productivity of the sunflower cultivar H358 (Dekalb), with the highest value of 2,101 kg ha -1 at the maximum estimated N dose of 55 kg ha -1 . The increment in N levels negatively affected the oil content in the achenes, while the increment in water salinity levels compromised the oil yield of sunflower achenes (Figure 6).…”
Section: Figure 2 Number Of Viable Achenes In Sunflower CV "Embrapasupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results were presented by Lobo et al (2012), who concluded that the increment in N levels from 50 to 130 kg ha -1 increased sunflower productivity from 2,152 to 3,802 kg ha -1 . These results also agree with those of Biscaro et al (2008), who observed that split N fertilisation as top-dressing at the doses of 0 to 80 kg ha -1 increased the productivity of the sunflower cultivar H358 (Dekalb), with the highest value of 2,101 kg ha -1 at the maximum estimated N dose of 55 kg ha -1 . The increment in N levels negatively affected the oil content in the achenes, while the increment in water salinity levels compromised the oil yield of sunflower achenes (Figure 6).…”
Section: Figure 2 Number Of Viable Achenes In Sunflower CV "Embrapasupporting
confidence: 92%
“…For the factor N levels, the data best fitted to a positive linear model, according to the regression equation (Figure 3), with increment from 13.91 to 17.51 cm in relation to the lowest and highest N levels (60 and 120 kg of N ha -1 ), which represented an increase of 11.64% for every 20 kg ha -1 of N applied to the soil, between the levels of 60 and 120 kg ha -1 . Although lower than 19.9 and 22.4 cm, obtained by Lobo and Grassi Filho (2007) in the soil without and with 50 kg ha -1 of N, these values surpass the value of 11.9 cm in the capitulum diameter of the sunflower cultivar H358 at the dose of 44.9 kg ha -1 of N reported by Biscaro et al (2008). In this context, Ivanoff et al (2010) claim that adequate N fertilisation management promotes increments of approximately 16% in the mean diameter of sunflower capitulum; this was also observed by Siddiqui et al (2009) …”
Section: Figure 2 Number Of Viable Achenes In Sunflower CV "Embrapacontrasting
confidence: 52%
See 1 more Smart Citation
“…Tomich et al (2003) found plant height of 2.05 m, whereas Biscaro et al (2008) estimated that the N dose of 73 kg ha -1 was associated with plant height of 1.15 m, which is inferior to the value found in the present study for a similar N dose (Figure 1). On the other hand, Schwerz et al (2016) did not observe effect of N fertilization on sunflower height.…”
Section: Resultscontrasting
confidence: 99%
“…Highest value of capitulum diameter (16.45 cm) was estimated for doses of 95 kg ha -1 of N + 120 kg ha -1 of P 2 O 5 (Y = 12.68 + 0.04768 ** N -0.0002509 * N 2 + 0.01261 ** P, R 2 = 0.67 - Figure 2B). Biscaro et al (2008) observed maximum stem diameter of 1.84 cm at the N dose of 48 kg ha -1 and maximum capitulum diameter of 11.9 cm at N dose of 45 kg ha -1 . Freitas et al (2012) found capitulum diameter of 15.38 cm with N application of 75 kg ha -1 .…”
Section: Resultsmentioning
confidence: 78%